Localizing Modern Subject In Haryanv iFolklore: A Conceptual Analisis - Devender, Kumar
Այս աշխատության մեջ դիտարկված է Հարյանվիի արդի բանահյուսությունը: Արդի բանահյուսական այս նկարագրությունը՝ որպես դեպի արդարություն և իրավունքներ ուղղված շարժում, ևս մեկ հարթակ է ավելացնում արդիականության մեծ բանավեճին: In this sense, folklore is a record of the local elements of modernity. In this paper the narrative of modernity is drawn from Haryanvi folklore. This folkloric account of modernity as a move towards justice and rights gives a different dimension to the grand discourse of modernity. Methods and materials: In this article, a few items from Haryanvi folklore - one folk dance, one folk joke and one real-life performer’s experiences-are being referred to to locate consciousness of justice and rights as the markers of modernity among the folk personae and performers in Haryanvi culture. Analysis: It focuses on the change of cultural institutions and interactions between communities. It analyses the rules, systems and values that underpin development. Results: The folklore items referred to in this article depict Haryanvi society as passing through a phase of self-renewing and self-transformation. And mobility is the primary harbinger of modernity as it brings different cultures in contact and provides a person a critical perspective to view one’s culture and society. В статье повествование о современности взято из фольклора Харьянви. Это фольклорное описание современности как движения к справедливости и правам придает иное измерение великому дискурсу современности. Методы и материалы: В этой статье рассмотрены несколько образцов из фольклора Харьянви - один народный танец, одна народная шутка и одно исполнение, чтобы определить сознание справедливости и прав, как маркеры современности среди фольклорных персонажей и исполнителей в культуре Харьянви. Анализ: Основное внимание уделяется изменению культурных институтов и взаимодействию между сообществами. Анализированы правила, системы и ценности, лежащие в основе развития. Результаты: Фольклорные произведения, упомянутые в этой статье, изображают общество Харьянви как проходящее через фазу самообновления и самопреобразования. А мобильность является основным предвестником современности, поскольку она приводит в контакт различные культуры и дает человеку критический взгляд на свою культуру и общество.
Keywords: Modern folklore